12-29-2021, 03:57 AM

Say that we have:

x=1-2t

and

y=(t^2)+4

And we want to write this as y=etc. How would we do so? I mean, I could just rewrite the top equation to t=1/2-x/2 and then put that into the lower y equation so that it would be y=((1/2-x/2)^2)+4. (Which can be simplified further to (1/4x^2)-(1/2x)+17/4.) But I bought the HP Prime so that I could be lazy. Not do actual work. XD

x=1-2t

and

y=(t^2)+4

And we want to write this as y=etc. How would we do so? I mean, I could just rewrite the top equation to t=1/2-x/2 and then put that into the lower y equation so that it would be y=((1/2-x/2)^2)+4. (Which can be simplified further to (1/4x^2)-(1/2x)+17/4.) But I bought the HP Prime so that I could be lazy. Not do actual work. XD